AI FOR IELTS WRITING PREPARATION: REVIEWING CHATGPT-GENERATED ANSWER MOCKUPS AND ITS TEXT EVALUATION - Andriani, Erina (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2025)
Generative AI (GenAI) tools, such as ChatGPT, are increasingly used as accessible, fast, and consistent alternatives for language proficiency exam preparation, especially for writing tasks. While GenAI tools are seen as efficient in providing feedback, little research has explored their role in generating answer mockups for IELTS writing tasks and evaluating the mockups they create. This study investigated the use of ChatGPT for IELTS General Training Writing Task 1 preparation by addressing these research questions: “How did ChatGPT generate answer mockups for IELTS General Training Writing Task 1?” and “How did ChatGPT evaluate the answer mockups it created?” This research employed qualitative content analysis, examining 15 mockups created for five IELTS writing prompts across score bands 6, 7, and 8. The findings showed that ChatGPT could generate mockups by adhering to IELTS task prompts and criteria in most cases. ChatGPT could also provide detailed evaluations and scores for each writing criterion. However, discrepancies between the generated mockups' scores and the evaluation scores raise questions about the consistency and accuracy of the assessments. The implications of this study are for ChatGPT as a more accessible option for IELTS preparation and as an evaluation of GenAI tools’ responses for future development.